The evolution of the value of women (Alternate Horizons, 2024)
When tradition and modernisation combine, we evolve to create a future of endless opportunities. Evolution is especially true for women and the value they bring to society and globally. This article speaks about the evolution that women and their value have gone through in the last few decades.